2013
DOI: 10.1097/mop.0b013e32835c1122
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the treatment of Kawasaki disease

Abstract: Although most practitioners in the USA use IVIG as a second-line therapy for those Kawasaki disease patients who have persistent or recrudescent fever, promising new therapies are under study. Infliximab and steroids are currently the two agents that have been most studied. However, larger studies and studies in genetically diverse populations are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 65 publications
(56 reference statements)
0
9
0
Order By: Relevance
“…if we were to include the patients who were treated in these connected general pediatric clinics/hospitals and could obtain data from every hospital that received the questionnaire (ie, 100% complete response), the incidence of Kd would then be higher than that in the present survey. 22 the recently published report of the raiSe study indicated that the addition of a steroid to the standard iVig treatment decreased coronary complications in the patients with severe Kd in Japan. in this regard, the optimal method for establishing the actual incidence of Kd is to use the national databases in taiwan (from the data of the national Health insurance Program) 10 and in California (from the data of the department of Public Health and the Centers for disease Control and Prevention's national Kd Surveillance System).…”
Section: Discussionmentioning
confidence: 98%
“…if we were to include the patients who were treated in these connected general pediatric clinics/hospitals and could obtain data from every hospital that received the questionnaire (ie, 100% complete response), the incidence of Kd would then be higher than that in the present survey. 22 the recently published report of the raiSe study indicated that the addition of a steroid to the standard iVig treatment decreased coronary complications in the patients with severe Kd in Japan. in this regard, the optimal method for establishing the actual incidence of Kd is to use the national databases in taiwan (from the data of the national Health insurance Program) 10 and in California (from the data of the department of Public Health and the Centers for disease Control and Prevention's national Kd Surveillance System).…”
Section: Discussionmentioning
confidence: 98%
“…A number of traditional laboratory and clinical findings have been built into scoring systems to predict IVIG resistance that are used in Japanese populations (52). These scoring systems (Sano, Kobayashi, Egami) all have relatively high sensitivity, near 80%, in Asian populations; however, they have poor predictive ability in heterogenous lower pretest probability populations of North America (53).…”
Section: Human Biomarkersmentioning
confidence: 99%
“…As this has not been shown to effect development of aneurysms, other platelet-aggregation inhibitors such as Clopidogrel or dipyridamole, can be considered in special situations (2). The main treatment modalities hoped to target prevention of coronary aneurysms used for refractory treatment are second doses of IVIG, steroids, calcineurin inhibitors, anti-IL-1 monoclonal antibodies, and anti-TNF monoclonal antibodies; all of which have broad immunological effects (53,161).…”
Section: Other Treatmentsmentioning
confidence: 99%
“…Because of the repair process, however, a stenosis can occur in the incoming or outgoing aneurysmal area, secondary to intimal hyperplasia or thrombotic occlusion, with risk of myocardial ischemia, heart attack, and unexpected death [ 59 ]. Long-term therapy in KD patients with CAA aims at prevention of cardiovascular sequelae, reduction of both frequency and severity of heart attacks, and improvement of patient’s quality of life [ 60 – 62 ]. Such therapy depends on the severity and extension of coronary artery involvement.…”
Section: Treatment Of the Cardiovascular Complications Of Kawasaki DImentioning
confidence: 99%